Hybrid Marketing Strategy for Optimizing Zakat, Infaq, and Sadaqah Collection: A Maqashid Shariah-Based Case Study in Jember Regency, Indonesia - M.F. Hidayatullah; Muchammad Abdur Rochman; Mahsyurotun Ni’mah (Journal of Islamic Economics Perspectives, 2025)
This study develops a hybrid marketing strategy to optimize the collection and distribution of zakat, infaq, and sedekah (ZIS) in Jember Regency, Indonesia. Despite increasing awareness of Islamic philanthropy, the potential of ZIS remains largely untapped, especially in semi-urban areas. This study contextualizes ZIS marketing within the Maqashid Syariah framework, emphasizing economic efficiency as well as ethical and spiritual dimensions. Using a qualitative case study approach with in-depth interviews, findings suggest that successful ZIS fundraising requires alignment with donor values, segmentation based on age and religiosity, and integration of digital platforms (social media, fintech applications) with offline strategies (lecture-based campaigns, community events). This study proposes a Maqashid-Based Hybrid Marketing Model that combines five elements: (1) targeted digital engagement, (2) offline trust-building mechanisms, (3) donor journey mapping for Gen Z and Millennials, (4) transparency-based ethical branding, and (5) value-based campaign themes. The novelty of this study lies in the integration of Maqashid Syariah principles into the Islamic philanthropic marketing framework, the adaptation of hybrid strategies in Indonesia's semi-urban environment, and the donor-centric model. This study contributes to the discourse of Islamic social finance by offering a scalable strategy to increase ZIS collection